Economic Feasibility of Nutrient-Rich Fertilizer Derived from Solid and Empty Fruit Bunches of Oil Palm - Setyawan, Onny; Renaldo, Nicholas; Suhardjo, Suhardjo; Tendra, Gusrio; Veronica, Kristy; Junaedi, Achmad Tavip; Tanjung, Amries Rusli (Luxury: Landscape of Business Administration, 2025)
This study aims to evaluate the economic feasibility of producing nutrient-rich fertilizers from solid fruit bunches (FBs) and empty fruit bunches of oil palm, taking into account nutrient composition, production process, cost structure, and potential market opportunities. This study bridges the gap between agricultural science and business economics by combining nutrient analysis of oil palm solids and empty fruit bunches with a cost-benefit evaluation and market potential assessment. This study used a mixed-methods design that combined: (1) experimental laboratory analysis (nutrient profiles and processing trials); (2) process mass balance and cost accounting to develop a production cost model; and (3) market and financial analysis (surveys, price benchmarking, and financial valuation). This study shows that solid palm oil waste, specifically solid decanter cake and empty fruit bunches (jangkos), contains significant macro and micronutrients that can be converted into high-value products such as organic fertilizer and soil conditioner. Provide palm oil mills with a science-based business model to convert waste into value-added products.